TAM Receptor Tyrosine Kinases: Biologic Functions, Signaling, and Potential Therapeutic Targeting in Human Cancer - Linger, Rachel M. A. (2008)
Tyro-3, Axl, and Mer constitute the TAM family of receptor tyrosine kinases (RTKs) characterized by a conserved sequence within the kinase domain and adhesion molecule-like extracellular domains. This small family of RTKs regulates an intriguing mix of processes, including cell proliferation/survival, cell adhesion and migration, blood clot stabilization, and regulation of inflammatory cytokine release. Genetic or experimental alteration of TAM receptor function can contribute to a number of disease states, including coagulopathy, autoimmune disease, retinitis pigmentosa, and cancer. In this chapter, we first provide a comprehensive review of the structure, regulation, biologic functions, and down-stream signaling pathways of these receptors. In addition, we discuss recent evidence which suggests a role for TAM receptors in oncogenic mechanisms as family members are over-expressed in a spectrum of human cancers and have prognostic significance in some. Possible strategies for targeted inhibition of the TAM family in the treatment of human cancer are described. Further research will be necessary to evaluate the full clinical implications of TAM family expression and activation in cancer.